Faith and Body: Welcoming the Theological Creed’s Corpus to Disability Amicable - Naibaho, Megawati; Bawono, Haryo Tejo; Sipahutar, Antonius P; Hutapea, Amelita; Zebua, Yasinta (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2025)
Our bodies tell God’s story. The Church regards the human body as sacred, intended for ultimate union with God, and anticipates it to be treated as a temple. The narrative suggests that we ought to regard our bodies with reverence and integrity, while anticipating their eventual resurrection. This appears to be a triumphalist perspective regarding the church's stance on the body. This theological conception has significantly influenced Church members in their pursuit of complete holiness throughout their lives, yet it has also resulted in serious repercussions, specifically subtle dualism and the issue of bodily imperfection. The Church's emphasis on the unity of body and soul, alongside the concept of the soul's immortality, generates a tension regarding the precedence of the soul's salvation over the body's welfare. This results in a disjunction between the ideal church and the actual church, leading to diminished attention towards non-triumphalistic groups, specifically individuals with disabilities. The corporeal form that narrates God's story is also the anthropological entity. The intersection of theology and anthropology in spirituality necessitates a discussion on both the sacramental essence of the body and the theological design for the body, culminating in the same conclusion: the body as a symbol of salvation rather than condemnation. This paper presents novel theological concepts that advocate for the marginalized, specifically individuals with disabilities. This paper aims to demonstrate that God's plan of salvation for His people, as articulated in the Nicene Creed and informed by John Paul II's theology of the body, is applicable both communally and personally, particularly concerning individuals with disabilities. In the end, we can hope a kind of inclusive theology to all people especially those with disability.